The Role of Instagram, Facebook, and YouTube Frequency of Use in University Students' Digital Skills Components - Maria Perifanou; Katerina Tzafilkou; Anastasios A. Economides (MDPI AG, 2021)
The literature provides rich evidence on students' levels of digital skills as well as on their frequency of Internet and social media use. Several studies have examined the relationships between social media use and academic achievement. However, there are not any studies investigating the relationships between social media use and digital skills of higher education students. To fill this research gap, this study examines the links between the frequency of social media use and students' digital skills. The survey was conducted with 155 university students in Greece. The instrument on six digital skills components was evaluated in terms of reliability and consistency. The research findings reveal a strong positive association between the use of YouTube and students' digital skills on content evaluation and protection. Age and educational level differences were noted in several digital skills components, whereas age and gender were related to the frequency of Instagram use. The main conclusion is that the generic use of Facebook and Instagram does not affect students' digital skills. However, combined literature evidence implies that when social media are used for educational purposes, they might influence students' perceived levels of digital skills. Implications and limitations are discussed in the study.